A low-carbon high-strength building material and preparation method thereof

By combining liquid monomers and coupling agents to build a bonding system, combined with in-situ polymerization technology, the problems of high energy consumption and high carbon emissions of traditional cement bonding systems are solved, and high-strength and low-carbon building materials are prepared, and the construction materials with high strength and low carbon are broadened. Range of utilization of solid particles.

CN119143428BActive Publication Date: 2025-02-14TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411604242.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The cement bonding system of traditional building materials has problems of high energy consumption and high carbon emissions during the production process, and it is difficult to effectively utilize solid particles of different properties, resulting in the depletion of river sand resources. The existing new low-carbon bonding system has problems of low bond strength, complex process and long time.

Method used

The bonding system is constructed by combining liquid monomers with coupling agents containing double bond functional groups. By knocking or shocking the mold, it is mixed with solid particles evenly to achieve in-situ polymerization, and low-carbon and high-strength building materials are prepared.

Benefits of technology

This method greatly reduces carbon emissions, the preparation process is simple and fast, and the compressive strength of the material can reach up to 190 MPa, far exceeding the highest national standards of ordinary bricks and concrete. It can effectively utilize solid particles of different properties such as desert sand and sea sand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143428B_ABST
    Figure CN119143428B_ABST
Patent Text Reader

Abstract

The present invention discloses a low-carbon high-strength building material and a preparation method thereof. The preparation method comprises: mixing a liquid monomer and a coupling agent containing a double-bond functional group in proportion to obtain a monomer binder; after deoxygenating the monomer binder, adding an initiator, and then adding it to a mold containing solid particles, and evenly mixing the materials by knocking or vibrating the mold, and finally initiating in-situ polymerization to obtain a low-carbon high-strength building material. After the liquid monomer that can form hydrogen bonds is used in combination with the coupling agent containing a double-bond functional group, it can quickly infiltrate the surface of the solid particles and enter the gaps between the solid particles before in-situ polymerization due to its low viscosity and strong fluidity, thereby realizing a self-assembly process. After in-situ polymerization occurs, the formed polymer can not only enhance the strength of the bonding system itself, but also firmly anchor the polymer chain on the surface of the solid particles. The building material prepared by this method has a compressive strength of up to 190 MPa, far exceeding the highest national standards for ordinary bricks and concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building material preparation, and more specifically, to a low-carbon high-strength building material and a preparation method thereof. Background Art

[0002] With the development of society and the acceleration of urbanization, the continued growth of the construction industry has led to an increasing demand for building materials. By 2021, my country's construction area has reached 15 billion square meters, and the total contract amount of the corresponding construction industry has reached 65 trillion yuan. However, the cement system, which is the largest bonding system used in traditional building materials, has problems of high energy consumption and high carbon emissions in the production process. The cement production process usually requires a high-temperature sintering process of about 1450°C, which consumes a lot of energy and causes huge carbon emissions, accounting for about 7% of the world's total carbon emissions. At the same time, the solid particles bonded by cement as a bonding system are very limited, and river sand can often only be used as aggregate. According to statistics, the global construction industry alone consumes up to 50 billion tons of river sand each year, which makes river sand resources rapidly depleted. At the same time, desert sand, sea sand and solid particles produced in some industrial production processes (such as slag and coal gangue) have not been effectively utilized due to their fine particle size, high chloride ion content and complex composition.

[0003] The new low-carbon bonding systems currently developed, such as biomineralization bonding systems and geopolymer bonding systems, have many problems such as low bonding strength, complex bonding process and long bonding time. In CN 115745473 A, a nano-modified low-temperature fast-solidification early-strength construction material is prepared by using an adhesive with polymethyl methacrylate and methyl methacrylate as the main components under the joint action of auxiliary agents such as crosslinking agents, coupling agents, initiators, modifiers and inorganic aggregates (such as standard sand, sea sand, river sand). However, since the adhesive contains a polymer with high viscosity, it is easy to destroy the original stacking mode of particles with smaller size or density when mixed with inorganic aggregates, and there will also be brittleness problems. In addition, the bonding scheme for solid particles such as desert sand, slag, steel slag, etc. that are more different from sea sand and river sand is also not involved. Therefore, it is still a severe challenge to develop a new bonding system to bond particles of different properties under mild and low-carbon emission conditions to prepare high-strength building materials. Summary of the invention

[0004] The first object of the present invention is to provide a method for preparing a low-carbon high-strength building material. The preparation method combines a liquid monomer that can form a hydrogen bond with a coupling agent containing a double-bond functional group to construct a bonding system, which replaces the traditional building adhesive cement, greatly reducing carbon emissions. In addition, due to the good fluidity of the liquid monomer, the coupling agent can be smoothly moved to the interface between the liquid monomer and the solid particles before polymerization, and the original stacking mode of the solid particles will not be changed. At the same time, the compressive strength of the prepared building material can reach up to 190 MPa, far exceeding the highest national standards for ordinary bricks and concrete.

[0005] The second object of the present invention is to provide a low-carbon, high-strength building material prepared using the preparation method described above.

[0006] In order to achieve the above first object, the present invention adopts the following technical scheme:

[0007] The present invention discloses a method for preparing a low-carbon high-strength building material, comprising the following steps:

[0008] Mixing a liquid monomer and a coupling agent containing a double bond functional group in proportion to obtain a monomer binder;

[0009] After the monomer binder is deoxygenated, an initiator is added, and the monomer binder containing the initiator is added into a mold containing solid particles, and the materials are mixed evenly by knocking or vibrating the mold, and finally in situ polymerization is initiated to obtain a low-carbon high-strength building material;

[0010] Generally, when solid materials are mixed with binders, external force is required to stir the materials evenly due to the high viscosity of the binders, which takes a long time and is complicated to operate. However, the present invention does not require a stirring process. After adding the materials to the mold, the mold can be knocked or shaken 3-20 times to mix them evenly, which is more convenient to operate.

[0011] Wherein, the liquid monomer is selected from one or more of methyl methacrylate, ethyl acrylate, hydroxyethyl methacrylate, methacrylic acid, hydroxyethyl acrylate, and glyceryl methacrylate;

[0012] The coupling agent is selected from one or more of vinyl trimethoxy silane, vinyl tri (β-methoxyethoxy silane), γ- (methacryloyloxy) propyl trimethoxy silane, and glycidyl methacrylate;

[0013] In the in-situ polymerization reaction, one end of the coupling agent forms a chemical bond with the surface of the solid particle through a chemical reaction, and the other end of the coupling agent undergoes a copolymerization reaction with the liquid monomer to form a polymer.

[0014] Furthermore, the mass ratio of the coupling agent to the liquid monomer is 1:99-30:70, and technicians can control the mechanical properties of the building materials prepared later by adjusting the ratio of the coupling agent to the liquid monomer in the monomer binder.

[0015] Furthermore, the viscosity of the initiator-containing monomer binder is 0.1 mPa·s-500 mPa·s / 25°C, and the ratio of the loss modulus G'' to the storage modulus G' (ie, the loss coefficient) is 100-100000, indicating that the monomer binder exhibits the characteristics of a liquid with strong fluidity.

[0016] Furthermore, the mass ratio of the initiator to the monomer binder is 1:20-1:200, and the mechanical properties of the building material prepared later can be controlled by controlling the ratio of the initiator to the monomer binder. The selection of the type of initiator can be changed accordingly according to the initiation method. For example, when a thermal initiation method is adopted, a thermal initiator can be added, and when a photoinitiation method is adopted, a photoinitiator can be added, which is not specifically limited here. Exemplarily, the initiator includes but is not limited to an organic peroxide initiator and / or an azo initiator.

[0017] Further, the azo initiator includes but is not limited to one or more of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate;

[0018] The organic peroxide initiator includes, but is not limited to, one or more of benzoyl peroxide, di-tert-butyl peroxide, diisopropyl peroxydicarbonate, methyl ethyl ketone peroxide, and diisopropyl peroxydicarbonate.

[0019] Furthermore, when the initiator is selected from an azo initiator, the mass ratio of the azo initiator to the monomer binder is 1:25-1:75.

[0020] Furthermore, when the initiator is selected from an organic peroxide initiator, the mass ratio of the organic peroxide initiator to the monomer binder is 1:75-1:125.

[0021] Furthermore, the solid particles are selected from one or more of quartz sand, sea sand, golden sand, pearl sand, desert sand and other sands with SiO2 as the main component and industrial waste particles (such as slag, coal slag, steel slag, etc.); illustratively, the particle size of the quartz sand is 100-250 μm, the particle size of the desert sand is 50-150 μm, the particle size of the sea sand is 300-500 μm, the particle size of the steel slag is 10-1000 μm, the particle size of the golden sand is 500-1000 μm; the particle size of the pearl sand is 2000-3000 μm.

[0022] Furthermore, the monomer binder deoxygenation method includes, but is not limited to, ultrasonicating the solution for 10-60 min, or introducing nitrogen into the solution for 30-120 min, which is not specifically limited here.

[0023] Furthermore, the mass ratio of the initiator-containing monomer binder to the solid particles is 1:2-1:5; illustratively, the mass ratio of the initiator-containing monomer binder to the solid particles can be 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, etc.

[0024] Furthermore, the in-situ polymerization may be initiated by heat or light.

[0025] Further, when thermal initiation is selected as the initiation method, the thermal initiation condition is heating in an oven at 40-85°C for 10-120min;

[0026] When light initiation is selected as the initiation method, the light initiation conditions are irradiation with ultraviolet light at a wavelength of 320-395nm for 5-60min.

[0027] In order to achieve the above second purpose, the present invention adopts the following technical solutions:

[0028] The invention discloses a low-carbon high-strength building material prepared by the preparation method as described above.

[0029] The beneficial effects of the present invention are as follows:

[0030] The present invention selects a coupling agent containing a double-bond functional group, a liquid monomer that can form a hydrogen bond, and an initiator to form a monomer binder with strong fluidity, low viscosity, and good wettability. The monomer binder is mixed with solid particles before polymerization, and can fully infiltrate the surface of solid particles and enter the gaps of particles through capillary penetration, so that the coupling agent molecules can smoothly move to the interface of the liquid monomer and the solid particles, and will not change the original stacking mode of the solid particles. The molecules in the binder can move freely, and a self-assembly process occurs, maximizing the interaction between the monomer binder and the surface of the solid particles. After the polymerization reaction occurs, one end of the coupling agent containing a double bond forms a chemical bond with the surface of the solid particles through a chemical reaction, and the other end can be polymerized with the liquid monomer, so that the solid particles are firmly bonded. The polymer produced by the monomer that can form a hydrogen bond after polymerization has high strength because it contains a large number of hydrogen bonds. Therefore, the block material obtained in this way has a higher compressive strength, which can reach up to 190 MPa, far exceeding the highest national standards for ordinary bricks and concrete, and can meet the application needs of various fields.

[0031] In the preparation process of the present invention, since no solvent is introduced, there is no need to remove the solvent in the later stage. The bonding process is fast and simple, and the traditional building adhesive cement is replaced, carbon emissions are greatly reduced, and the use is more environmentally friendly.

[0032] The invention can make full use of desert sand, sea sand and solid particles produced in some industrial production processes as building aggregates, broadens the selection range of raw materials, and the obtained building materials have high mechanical properties and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0034] Figure 1 The forming process of the building material provided by the present invention is shown;

[0035] in, Figure 1 In a, liquid monomers and coupling agents use capillary force to enter between particles and the molecules self-assemble. Figure 1 In b, the monomers are polymerized in situ to form polymers, thereby improving the strength of the bonding system. At the same time, the polymer chains are chemically anchored on the surface of the solid particles through coupling agents, ultimately achieving firm bonding of the solid particles.

[0036] Figure 2 The stress-strain curves of the samples prepared in Examples 1-6 are shown.

[0037] Figure 3 The test spectrum of the sample prepared in Example 1 after 10,000 cycles of compression is shown.

[0038] Figure 4 The stress-strain curves of the samples prepared in Examples 7-9 are shown.

[0039] Figure 5 The stress-strain curves of the samples prepared in Comparative Examples 1-2 are shown. DETAILED DESCRIPTION

[0040] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0041] See also Figure 1In the present invention, by combining a coupling agent containing a double bond functional group with a liquid monomer that can form a hydrogen bond, it is found that before the polymerization reaction, the monomer binder composed of the liquid monomer and the coupling agent has good fluidity, and can quickly infiltrate the surface of the solid particles and enter the gaps between the solid particles through capillary penetration, so that the coupling agent molecules can smoothly move to the interface between the liquid monomer and the solid particles, generate interfacial interaction, and will not change the original stacking mode of the solid particles. This is also the reason why the binder and the solid particles can be evenly mixed by simple vibration methods such as knocking or shaking the mold; after the polymerization reaction occurs, the liquid monomer is converted into a polymer. At the same time, one end of the coupling agent in the monomer binder forms a chemical bond with the surface of the solid particles through a chemical reaction, and the other end of the coupling agent undergoes a copolymerization reaction with the liquid monomer, which can maximize the interfacial interaction for fixation while improving the body strength of the bonding system, which is conducive to the preparation of high-strength building materials. Therefore, the bonding system provided by the present invention is to bond solid particles through a bulk polymerization process rather than a polymer cross-linking process. The solid particles, as a heat dissipation medium, can absorb a large amount of heat generated by free radical polymerization. In addition, since the bonding system does not contain a solvent, the material will not produce pores inside due to solvent volatilization after molding, which is conducive to further improving the strength of the material. The bonding system provided by the present invention can replace traditional building binder cement, greatly reducing carbon emissions, and can bond desert sand, sea sand and solid particles (such as slag, coal gangue, etc.) generated in some industrial production processes, and the compressive strength of the resulting building materials can reach 80-190 MPa, meeting the application needs of various fields.

[0042] Synthesis example

[0043] γ-(Methacryloyloxy)propyltrimethoxysilane and hydroxyethyl methacrylate were mixed in different proportions to obtain monomer binders, and the viscosity and modulus data of each monomer binder were tested (the test temperature was 25° C.), and the results are shown in Table 1. From the results, it can be seen that the binder system provided by the present invention has lower viscosity and better fluidity, and the monomer binder exhibits liquid characteristics with strong fluidity.

[0044] Table 1

[0045]

[0046] Example 1

[0047] γ-(methacryloyloxy)propyltrimethoxysilane and hydroxyethyl methacrylate are mixed in a mass ratio of 10:90 to obtain a monomer binder;

[0048] The monomer binder was deoxygenated by nitrogen for 30 min, azobisisobutyronitrile was added as an initiator, the mass ratio of the initiator to the monomer binder was 1:50, and ultrasonic deoxygenation was performed again for 1.5 min to obtain a monomer binder containing an initiator;

[0049] Add quartz sand into the silicone mold to fill the silicone mold, add the monomer binder containing the initiator into the silicone mold filled with quartz sand, the mass ratio of the monomer binder containing the initiator to the quartz sand is 4:11, and compact the silicone mold on the flat ground for 3 times to evenly mix the monomer binder and quartz sand inside, then initiate polymerization in a 60°C oven for 1 hour, and remove the mold to obtain a building material sample.

[0050] The obtained building material samples were subjected to compression test according to GB / T 2567-2021 and the compression stress-strain curve was obtained. Figure 2 , and its compressive strength is 191 MPa.

[0051] The obtained building material samples were compressed 10,000 times under 80 MPa pressure. Figure 3 , and found that the building material sample has good pressure bearing capacity.

[0052] Example 2

[0053] γ-(methacryloyloxy)propyltrimethoxysilane and hydroxyethyl methacrylate are mixed in a mass ratio of 10:90 to obtain a monomer binder;

[0054] The monomer binder was ultrasonically deoxygenated for 20 min, azobisisobutyronitrile was added as an initiator, the mass ratio of the initiator to the monomer binder was 1:25, and ultrasonic deoxygenation was performed again for 1 min to obtain a monomer binder containing an initiator;

[0055] Add quartz sand into the polytetrafluoroethylene mold to fill the polytetrafluoroethylene mold, add the monomer binder containing the initiator into the polytetrafluoroethylene mold filled with quartz sand, the mass ratio of the monomer binder containing the initiator to the quartz sand is 4:11, and tamp the polytetrafluoroethylene mold on the flat ground for 3 times to evenly mix the monomer binder and quartz sand inside, then initiate polymerization in a 60°C oven for 1 h, and remove the mold to obtain a building material sample.

[0056] The obtained building material samples were subjected to compression test according to GB / T 2567-2021 and the compression stress-strain curve was obtained. Figure 2 , and its compressive strength is 159 MPa.

[0057] Example 3

[0058] γ-(methacryloyloxy)propyltrimethoxysilane and hydroxyethyl methacrylate are mixed in a mass ratio of 10:90 to obtain a monomer binder;

[0059] The monomer binder was ultrasonically deoxygenated for 20 min, azobisisobutyronitrile was added as an initiator, the mass ratio of the initiator to the monomer binder was 1:50, and ultrasonic deoxygenation was performed again for 1 min to obtain a monomer binder containing an initiator;

[0060] Add desert sand into the silicone mold to fill the silicone mold, add the monomer binder containing the initiator into the silicone mold with desert sand, the mass ratio of the monomer binder containing the initiator to the desert sand is 4:12, and press the silicone mold on the flat ground for 3 times to mix the monomer binder and desert sand inside evenly, then initiate polymerization in a 60°C oven for 1 hour, and remove the mold to obtain the building material sample.

[0061] The obtained building material samples were subjected to compression test according to GB / T 2567-2021 and the compression stress-strain curve was obtained. Figure 2 , and its compressive strength is 140 MPa.

[0062] Example 4

[0063] γ-(methacryloyloxy)propyltrimethoxysilane and hydroxyethyl methacrylate are mixed in a mass ratio of 10:90 to obtain a monomer binder;

[0064] The monomer binder was ultrasonically deoxygenated for 20 min, azobisisobutyronitrile was added as an initiator, the mass ratio of the initiator to the monomer binder was 1:50, and ultrasonic deoxygenation was performed again for 1.5 min to obtain a monomer binder containing an initiator;

[0065] Add sea sand into the polytetrafluoroethylene mold to fill the polytetrafluoroethylene mold, add the monomer binder containing the initiator into the polytetrafluoroethylene mold filled with sea sand, the mass ratio of the monomer binder containing the initiator to the sea sand is 4:12, and the polytetrafluoroethylene mold is compacted on the flat ground for 3 times to make the monomer binder and the sea sand inside evenly mixed, and then initiate polymerization in a 60°C oven for 1 h, and remove the mold to obtain a building material sample.

[0066] The obtained building material samples were subjected to compression test according to GB / T 2567-2021 and the compression stress-strain curve was obtained. Figure 2 , and its compressive strength is 161 MPa.

[0067] Example 5

[0068] γ-(methacryloyloxy)propyltrimethoxysilane and hydroxyethyl methacrylate are mixed in a mass ratio of 10:90 to obtain a monomer binder;

[0069] The monomer binder was ultrasonically deoxygenated for 20 min, azobisisobutyronitrile was added as an initiator, the mass ratio of the initiator to the monomer binder was 1:50, and ultrasonic deoxygenation was performed again for 1.5 min to obtain a monomer binder containing an initiator;

[0070] Steel slag is added into a polytetrafluoroethylene mold to fill the polytetrafluoroethylene mold, and a monomer binder containing an initiator is added into the polytetrafluoroethylene mold containing steel slag, the mass ratio of the monomer binder containing an initiator to the steel slag is 4:15, and the polytetrafluoroethylene mold is compacted on a flat ground for 5 times to evenly mix the monomer binder and steel slag inside, and then polymerization is initiated in an oven at 60°C for 1 h, and the mold is removed to obtain a building material sample.

[0071] The obtained building material samples were subjected to compression test according to GB / T 2567-2021 and the compression stress-strain curve was obtained. Figure 2 , and its compressive strength is 121 MPa.

[0072] Example 6

[0073] Mixing γ-(methacryloyloxy)propyltrimethoxysilane and hydroxyethyl methacrylate in a mass ratio of 20:80 to obtain a monomer binder;

[0074] The monomer binder was ultrasonically deoxygenated for 20 min, azobisisobutyronitrile was added as an initiator, the mass ratio of the initiator to the monomer binder was 1:50, and ultrasonically deoxygenated again for 2 min to obtain a monomer binder containing an initiator;

[0075] Add quartz sand into the silicone mold to fill the silicone mold, add the monomer binder containing the initiator into the silicone mold filled with quartz sand, the mass ratio of the monomer binder containing the initiator to the quartz sand is 4:11, and compact the silicone mold on the flat ground for 3 times to evenly mix the monomer binder and quartz sand inside, then initiate polymerization in a 60°C oven for 1 hour, and remove the mold to obtain a building material sample.

[0076] The obtained building material samples were subjected to compression tests and the compression stress-strain curves were obtained, see Figure 2 , and its compressive strength is 139 MPa.

[0077] Example 7

[0078] Vinyl trimethoxysilane, glycidyl methacrylate and hydroxyethyl methacrylate were mixed in a mass ratio of 5:45:50 to obtain a monomer binder having a viscosity of 4.05 mPa·s.

[0079] The monomer binder was ultrasonically deoxygenated for 15 min, azobisisobutyronitrile was added as an initiator, the mass ratio of the initiator to the monomer binder was 1:50, and ultrasonically deoxygenated again for 1.5 min to obtain a monomer binder containing an initiator;

[0080] Add quartz sand into the silicone mold to fill the silicone mold, add the monomer binder containing the initiator into the silicone mold filled with quartz sand, the mass ratio of the monomer binder containing the initiator to the quartz sand is 4:11, and compact the silicone mold on the flat ground for 3 times to evenly mix the monomer binder and quartz sand inside, then initiate polymerization in a 60°C oven for 1 hour, and remove the mold to obtain a building material sample.

[0081] The obtained building material samples were subjected to compression test according to GB / T 2567-2021 and the compression stress-strain curve was obtained. Figure 4 , its compressive strength is 135MPa.

[0082] Example 8

[0083] Vinyltrimethoxysilane and methyl methacrylate were mixed in a mass ratio of 10:90 to obtain a monomer binder having a viscosity of 0.57 mPa·s.

[0084] The monomer binder was ultrasonically deoxygenated for 15 min, and benzoyl peroxide was added as an initiator, with the mass ratio of the initiator to the monomer binder being 1:100, to obtain a monomer binder containing an initiator;

[0085] Add quartz sand into the silicone mold to fill the silicone mold, add the monomer binder containing the initiator into the silicone mold filled with quartz sand, the mass ratio of the monomer binder containing the initiator to the quartz sand is 4:11, and compact the silicone mold on the flat ground for 3 times to evenly mix the monomer binder and quartz sand inside, then initiate polymerization in an oven at 80°C for 4 hours, and remove the mold to obtain a building material sample.

[0086] The obtained building material samples were subjected to compression test according to GB / T 2567-2021 and the compression stress-strain curve was obtained. Figure 4 , and its compressive strength is 91 MPa.

[0087] Example 9

[0088] γ-(methacryloyloxy)propyltrimethoxysilane, methyl methacrylate and methacrylic acid were mixed in a mass ratio of 10:30:60 to obtain a monomer binder having a viscosity of 1.02 mPa·s;

[0089] The monomer binder was ultrasonically deoxygenated for 15 min, azobisisobutyronitrile was added as an initiator, the mass ratio of the initiator to the monomer binder was 1:50, and ultrasonically deoxygenated again for 1 min to obtain a monomer binder containing an initiator;

[0090] Add quartz sand into the silicone mold to fill the silicone mold, add the monomer binder containing the initiator into the silicone mold filled with quartz sand, the mass ratio of the monomer binder containing the initiator to the quartz sand is 4:11, and compact the silicone mold on the flat ground for 3 times to evenly mix the monomer binder and quartz sand inside, then initiate polymerization in a 60°C oven for 1 hour, and remove the mold to obtain a building material sample.

[0091] The obtained building material samples were subjected to compression test according to GB / T 2567-2021 and the compression stress-strain curve was obtained. Figure 4 , and its compressive strength is 141 MPa.

[0092] Comparative Example 1

[0093] γ-(methacryloyloxy)propyltrimethoxysilane and hydroxyethyl methacrylate were mixed in a mass ratio of 50:50 to obtain a monomer binder;

[0094] The monomer binder was deoxygenated by nitrogen for 30 min, azobisisobutyronitrile was added as an initiator, the mass ratio of the initiator to the monomer binder was 1:50, and ultrasonic deoxygenation was performed again for 1.5 min to obtain a monomer binder containing an initiator;

[0095] Add quartz sand into the silicone mold to fill the silicone mold, add the monomer binder containing the initiator into the silicone mold filled with quartz sand, the mass ratio of the monomer binder containing the initiator to the quartz sand is 4:11, and compact the silicone mold on the flat ground for 3 times to evenly mix the monomer binder and quartz sand inside, then initiate polymerization in a 60°C oven for 1 hour, and remove the mold to obtain a building material sample.

[0096] The obtained building material samples were subjected to compression test according to GB / T 2567-2021 and the compression stress-strain curve was obtained. Figure 5 , and its compressive strength is 51 MPa.

[0097] Comparative Example 2

[0098] γ-(methacryloyloxy)propyltrimethoxysilane and hydroxyethyl methacrylate are mixed in a mass ratio of 10:90 to obtain a monomer binder;

[0099] The monomer binder was deoxygenated by nitrogen for 30 min, azobisisobutyronitrile was added as an initiator, the mass ratio of the initiator to the monomer binder was 1:125, and ultrasonic deoxygenation was performed again for 1.5 min to obtain a monomer binder containing an initiator;

[0100] Add quartz sand into the silicone mold to fill the silicone mold, add the monomer binder containing the initiator into the silicone mold filled with quartz sand, the mass ratio of the monomer binder containing the initiator to the quartz sand is 4:11, and compact the silicone mold on the flat ground for 3 times to evenly mix the monomer binder and quartz sand inside, then initiate polymerization in a 60°C oven for 1 hour, and remove the mold to obtain a building material sample.

[0101] The obtained building material samples were subjected to compression test according to GB / T 2567-2021 and the compression stress-strain curve was obtained. Figure 5 , and its compressive strength is 31 MPa.

[0102] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a low-carbon high-strength building material, characterized in that: The steps include: Mixing a liquid monomer and a coupling agent containing a double bond functional group in proportion to obtain a monomer binder; After the monomer binder is deoxygenated, an initiator is added, and the monomer binder containing the initiator is added into a mold containing solid particles, and the materials are mixed evenly by knocking or vibrating the mold, and finally in situ polymerization is initiated to obtain a low-carbon high-strength building material; Wherein, the liquid monomer is selected from one or more of methyl methacrylate, ethyl acrylate, hydroxyethyl methacrylate, hydroxyethyl acrylate, and glyceryl methacrylate; The coupling agent is selected from one or more of vinyl trimethoxy silane, vinyl tri (β-methoxyethoxy silane), γ- (methacryloyloxy) propyl trimethoxy silane, and glycidyl methacrylate; In the in-situ polymerization reaction, one end of the coupling agent forms a chemical bond with the surface of the solid particle through a chemical reaction, and the other end of the coupling agent copolymerizes with the liquid monomer to form a polymer; The mass ratio of the coupling agent to the liquid monomer is 1:99-30:70; The mass ratio of the initiator-containing monomer binder to the solid particles is 1:2-1:5; The viscosity of the initiator-containing monomer binder is 0.1 mPa·s-500 mPa·s / 25°C.

2. The preparation method according to claim 1, characterized in that: The ratio of the loss modulus G'' to the storage modulus G' of the monomer binder containing the initiator is 100-100000.

3. The preparation method according to claim 1, characterized in that: The solid particles are selected from one or more of quartz sand, sea sand, golden sand, pearl sand, desert sand and industrial waste particles.

4. The preparation method according to claim 1, characterized in that: The in situ polymerization can be initiated by heat or light.

5. The preparation method according to claim 1, characterized in that: The initiator is selected from organic peroxide initiators and / or azo initiators.

6. The preparation method according to claim 5, characterized in that: The initiator is selected from azo initiators, and the mass ratio of the azo initiator to the monomer binder is 1:25-1:75; or The initiator is selected from organic peroxide initiators, and the mass ratio of the organic peroxide initiator to the monomer binder is 1:75-1:

125.

7. The preparation method according to claim 4, characterized in that: The conditions for the thermally initiated polymerization are heating in an oven at 40-85° C. for 10-120 min; The conditions for the photo-initiated polymerization are irradiation with ultraviolet light at a wavelength of 320-395 nm for 5-60 minutes.

8. A low-carbon, high-strength building material, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Nano-modified low-temperature fast-curing early-strength building material and preparation method thereof

    CN115745473A